Osady organiczne doliny Płoni w Barlinku = Organic sediments of Płonia river valley in Barlinek - Gontaszewska-Piekarz, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents a detailed description of complicated geological structure of fragment of Płonia river valley in Barlinek. Płonia river made use a gutter eroded in end moraine of Pomeranian phase of Weichsel glaciations. There occurs two complexes of sediment: Pleistocene and Holocene. Pleistocene sediments have glacial, fluvioglacial and marginal lake origin, and Holocene sediments have lake, swamp and river origin.
Keywords: osady organiczne; dolina rzeczna; Płonia; Barlinek; organie sediments; river valley